Repellent action and contact toxicity mechanisms of the essential oil extracted from Chinese chive against Plutella xylostella larvae. Issue 1 (2nd November 2018) - Gao, Quan; Song, Li; Sun, Jia; Cao, Hai‐Qun; Wang, Likun; Lin, Huafeng; Tang, Feng
Abstract: Botanical pesticides play increasingly important roles in the control of agricultural pests. In this study, the insecticidal effects, specifically the repellent action and contact toxicity, of the essential oil extracted from Chinese chive (EOC) against Plutella xylostella larvae were confirmed. The mechanisms of repellent's action were studied using electroantennograms (EAGs), and the effects on glutathione S ‐transferase (GST), carboxylesterase (CarE), and acetyl cholinesterase were investigated after EOC treatments. The EOC affected the EAG results and inhibited the activities of GST and CarE in treated P. xylostella larvae, which could explain its insecticidal effects. And, four pyrazines showed greater repellent activities than that of the EOC, which was confirmed as the main active compounds of EOC.